KONSEP ISLAMISASI SAINS ILMU PENGETAHUAN DAN PENERAPANNYA DALAM PENDIDIKAN - Kamal; Usman, Syahruddin; Ondeng, Syarifuddin; Dian Asri Unga Mega (Program Studi Pendidikan Teknologi Informasi Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
This research explores the concept of Islamization of science and its application in education. Currently, there are still many parties who feel doubtful about the existence of Islamic science. Not a few of these parties are Muslims too. They consider the discourse on Islamic science and the Islamization of science to be absurd, because science is neutral. Logically, according to them, nature looks the same to everyone, whether Muslims, Christians, Hindus, Buddhists or any religion. The aim of writing this article is to explore further the concept of Islamization of science. This research uses a qualitative approach because it aims to understand the phenomenon in depth and holistically. This approach is suitable for exploring the views, experiences and interpretations of various parties regarding critical issues in Islamic education and religious moderation. The method used in writing this paper is to use the library method, namely by searching and collecting several sources from the internet and books regarding information regarding the concept of Islamization of science. The results of research on the concept of Islamization of Science show that the development of science and technology can be a means of getting closer to Allah, strengthening faith, and contributing goodness to humanity, as long as it is carried out with full awareness of religious values and moral responsibility